2001
DOI: 10.1034/j.1399-0012.2001.150409.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐transplant cardiac testing for kidney–pancreas transplant candidates and association with cardiac outcomes

Abstract: Clinical history alone is highly suggestive but not sufficient for the prediction of post-kidney-pancreas transplant myocardial infarction. Although a useful supplement, cardiac testing does not predict all cardiac events out to 1 yr post-testing. In this high-risk patient population with diabetes and renal failure, other methods of risk assessment are needed to more accurately predict long-term cardiac outcome for patients awaiting transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…There are, however, several single-center cohort studies of asymptomatic "low-risk" CKD patients (age <50 y, no diabetes, no history of CV disease), in which a high predictive value of ECG and chest X-ray for CV risk assessment was confirmed [13,28,37], and in which no other screening tests were performed before KT.…”
Section: Discussionmentioning
confidence: 98%
“…There are, however, several single-center cohort studies of asymptomatic "low-risk" CKD patients (age <50 y, no diabetes, no history of CV disease), in which a high predictive value of ECG and chest X-ray for CV risk assessment was confirmed [13,28,37], and in which no other screening tests were performed before KT.…”
Section: Discussionmentioning
confidence: 98%
“…Historically, angiocardiography was recommended for cardiac assessment; however, with the emergence of more sophisticated radiological cardiac imaging modalities, there has been a trend away from this invasive investigation. Stress echocardiography has also been used for cardiac stratification , while in our unit the mainstay of pretransplant assessment is myocardial perfusion scanning, as it offers the advantage of sensitive and detailed functional assessment in these high‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, 20% of subjects with negative dobutamine stress echocardiography results followed for 22 months reached a cardiac end point (12). In fact, a study in kidneypancreas transplant candidates found that most cardiac events occurred in individuals with negative results of noninvasive tests (32). Therefore, intensive medical therapy was recommended for all subjects with any angiographic evidence of CAD.…”
Section: Prediction Of a Low-risk Subgroupmentioning
confidence: 99%